AI INTEGRATION INTO PUBLIC ADMINISTRATION IN AFRICA: NAVIGATING COMPLEXITIES, INCLUSION, AND INSTITUTIONAL GAPS - Mickson, Michael K; Zilevu, Timothy Kwabla; Asamoah, Emmanuel; Kubi, Michael (ShodhKosh: Journal of Visual and Performing Arts, 2026)
This study will discuss the integration of artificial intelligence (AI) in the public administration of Africa by using three main strategic documents: E-Government Survey 2024, Ghana Digital Economy Policy and Strategy 2024, and the Continental AI Strategy 2024. The results indicate that although AI has become viewed as a revolutionary resource to enhance service delivery, efficiency in governance, and administrative responsibility, there is no concerted effort in adoption, and it is mainly policy-based rather than practice-based. The young African population is often described as a strategic resource in terms of AI-enabled innovation in the public sector, but a structural lack of STEM education, digital infrastructure, AI-related skills, and innovation ecosystems has limited the youth's preparedness a great deal. AI implementation has several ethical/regulatory gaps; this is primarily due to algorithmic bias, lack of data protection, and lack of accountability. These gaps pose formidable hurdles to promoting responsible AI use. The study, based on the frameworks of the Street-Level Bureaucracy and Technology Acceptance Model, reveals through a qualitative study of the documents that African systems of governance have many discrepancies between strategic plans and practical implementation capability. The study concludes that Africa is at a crossroads that needs climatic efforts at the continental level, human capital investment, strong regulatory implementation, and youth-focused innovation systems to make sure that AI usage is universal, moral, and development-driven. The expansion and validation of these findings by mixed-method and country-level empirical research should be included in future research.